Helicenes on Surfaces: Stereospecific On-Surface Chemistry, Single Enantiomorphism, and Electron Spin Selectivity - Ernst, Karl-Heinz (Chirality, 2024)
Helicenes represent an important class of chiral organic material with promising optoelectronic properties. Hence, functionalization of surfaces with helicenes is a key step towards new organic material devices. This review presents different aspects of adsorption and modification of metal surfaces with different helicene species. Topics addressed are chiral crystallization, that is, 2D conglomerate versus racemate crystallization, breaking of mirror-symmetry in racemates, chirality-induced spin selectivity, and stereoselective on-surface chemistry.
Keywords: on‐surface chemistry; helicenes; scanning tunneling microscopy; CISS; surface science